Efforts of State-Owned Enterprises (SOE) in Disseminating Pancasila by Actualizing Tri Hita Karana (THK) - I Gusti Ngurah Santika; I Nengah Suastika (JED (Jurnal Etika Demokrasi), 2022)
This research aims to determine the efforts of SOE in disseminating Pancasila by actualizing Tri Hita Karana. This type of research is descriptive qualitative. Data was collected by means of documentation. The results of this research indicated that the dissemination of Pancasila by SOE through the actualization of Tri Hita Karana can be seen from the ESR and CSR. The harmonious relationship between SOE and God is carried out through SOE activities that are oriented towards supporting the community in religion, for example building houses of worship, Ramadan package support, Iftar with Orphans, Hajj support, Tirtayatra, Pilgrimage, and religious discussions, as well as spiritual development. The dissemination of Pancasila through the actualization of Tri Hita Karana, especially in establishing a harmonious relationship with the environment is carried out by SOE through investment in the environmentally friendly sector, maintaining a balance in the exploitation of natural resources, and waste treatment (waste recycling). The dissemination of Pancasila through the actualization of Tri Hita Karana by SOE in building harmonious relations with humans is reflected in their concern for the community by empowering them socially and economically, education/training, improving health, organizing public facilities and infrastructure.Penelitian ini bertujuan untuk mengetahui upaya BUMN dalam mendiseminasikan Pancasila dengan mengaktualisasikan Tri Hita Karana. Jenis penelitian ini adalah deskriptif kualitatif. Pengumpulan data dilakukan dengan studi dokumentasi. Hasil penelitian ini menunjukan diseminasi Pancasila oleh BUMN melalui aktualisasi Tri Hita Karana dapat dilihat dari TJSL dan CSRnya. Hubungan harmonis antara BUMN dengan Tuhan dilakukan melalui kegiatan BUMN yang orientasinya mendukung masyarakat dalam keagamaan, misalnya membangun rumah ibadah, bantuan paket Ramadhan, Buka Puasa Bersama Anak Yatim, bantuan naik haji, Tirtayatra, Ziarah, dan diskusi keagamaan, serta pembinaan rohani. Diseminasi Pancasila melalui aktualisasi Tri Hita Karana, terutama dalam menjalin hubungan harmonis dengan lingkungan dilakukan BUMN melalui investasi pada sektor ramah lingkungan, menjaga keseimbangan eksploitasi sumber daya alam, pengolahan limbah (daur ulang limbah). Diseminasi Pancasila melalui aktualisasi Tri Hita Karana oleh BUMN dalam membangun hubungan harmonis dengan manusia tercermin dari kepeduliannya kepada masyarakat dengan memberdayakan secara sosial dan ekonominya, pendidikan/pelatihan, peningkatan kesehatan, penyelenggaraan sarana, dan prasarana umum.